(untitled) (Global Journal of Management and Business Research, 2013)
Purpose – This paper aims to explore how green branding towards beauty products can influence brand effect from the perspective Malaysian customers. The paper also aims to examine the components impact of green brand awareness, brand image, brand credibility, brand community and brand engagement and their positive relationship between them. This research study focuses on environmentally friendly beauty products available in Malaysia. Design/methodology/approach – This study employyed both quantitative and qualitative approach. A total of 30 respondents made up the focus groups and 200 respondents who had the experience of purchasing environmentally friendly products.were selected for the survey. Findings – The results of the study demonstrated that green brand awareness, brand image, brand credibility, brand community and brand engagement are positively related to branding of a business entity for beauty related product. Therefore, investing on resources to increase green brand awareness, brand image, brand credibility, brand community and brand engagement are helpful to enhance companies. Research limitations/implications – While the results are clear and have strong salience towards environmental beauty products industry in Malaysia, applications of the findings beyond Malaysia should take into account other factors such as the nature of industry, the perception, behavior and demographics of these customers. Practical implications – The study provides a set of findings relating to green branding initiatives that could be readily incorporated into a business plan. Originality/value – The study will be significant towards managers, researchers, and governments agencies, and provide useful contribution to relevant studies and future researches as reference.